PENERAPAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) SEBAGAI MEDIA PEMBELAJARAN DI SMPN 3 TERISI INDRAMAYU - Eko Arif Syaefudin; Ahmad Kholil; Dyah Arum Wulandari; Ratu Amilia Avianti; Djoko Walujo (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract SMPN 3 Terisi Indramayu is located on Raya Cikedung Street - Terisi, Indramayu Regency, West Java Province. This school is located in the supervision area of UNJ and its position is about 177 km from UNJ. The problem with analysis on the school location is currently being faced there are no learning media of a Solar Power Plant (PLTS) model that can improve students' ability to understand energy conversion theory. The increasing electricity costs also burden the finances of schools whose operational costs rely on School Operation Cost Support by Ministry. Utilization of renewable energy sources of solar power in the school environment is very suitable because it is located in the Pantura Jawa area which has high solar intensity. The solution offered is the application of PLTS as a learning media for students to understand about conversion energy system from solar energy into electrical energy system. The implementation of the activities has been implementation on September 24, 2022, which includes equipment installation and user training. The results of the activity show that PLTS devices with 3 x 120 wp can function properly. The input voltage and amperage indicators, battery voltage and amperage, and the resulting output in AC and DC voltages can turn on the load in the form of lights and fans. The training on the use of tools was opened by the principal and attended by students and teachers of SMPN 3 Terisi. They were enthusiastic about participating in the activities until the end of the event. Abstrak SMPN 3 Terisi Indramayu berada di Jalan Raya Cikedung - Terisi, Kecamatan Terisi, Kabupaten Indramayu Provinsi Jawa Barat. Sekolah ini berada pada wilayah binaan Universitas Negeri Jakarta dan posisinya sekitar 177 km dari Universitas Negeri Jakarta. Permasalah mitra yang dihadapi sekarang ini adalah belum adanya media pembelajaran berupa model Pembangkit Listrik Tenaga Surya (PLTS) yang dapat meningkatkan kemampuan siswa dalam memahami teori konversi energi. Biaya listrik semakin besar juga membebani keuangan sekolah yang biaya operasionalnya mengandalkan BOS. Pemanfaatan sumber energi terbarukan tenaga surya di lingkungan sekolah sangat cocok karena berada di daerah pantura yang memiliki intensitas matahari tinggi. Solusi yang ditawarkan adalah penerapan PLTS sebagai Media Pembelajaran siswa dalam memahami konversi energi dari energi matahari menjadi energi listrik. Pelaksanaan kegiatan telah dilaksanakan pada 24 September 2022 yang meliputi instalasi alat dan pelatihan penggunaan. Hasil kegiatan menunjukkan perangkat PLTS dengan 3 x 120 wp dapat berfungsi dengan baik. Indikator tegangan dan ampere masukan, tegangan dan ampere battere, serta output yang dihasilkan berupa tegangan AC dan DC dapat menyalakan beban berupa lampu dan kipas angin. Pelatihan penggunaan alat dibuka oleh kepala sekolah dan diikuti oleh siswa serta guru SMPN 3 Terisi yang cukup antusias mengikuti kegiatan sampai akhir acara.